3D LES simulations of a static and vertically free-to-oscillate 4:1 rectangular cylinder: Effects of the grid resolution. Issue 192 (September 2019) - Álvarez, A.J.; Nieto, F.; Nguyen, D.T.; Owen, J.S.; Hernández, S.
Abstract: Vortex induced vibration (VIV) is an important phenomenon which appears in flexible structures immersed in a moving fluid. This oscillation is self-sustained and self-limited, but VIV might cause fatigue damage and affect the structure's serviceability. In the present study, the aerodynamics of the flow fields around a static and vertically free-to-oscillate 4:1 rectangular cylinder are analysed by means of 3D LES simulations, adopting the OneEqEddy viscosity model. Integral parameters, pressure distributions, amplitudes of oscillation, coherences and correlations are obtained and compared with the available experimental data. Aiming to ascertain the impact of the boundary conditions and the grid resolution on the accuracy of results, five cases adopting 3 different meshes including two different spanwise discretisations have been considered. When studying the aerodynamics of the cylinder in static conditions, the influence of the spatial discretisation is very limited, and the agreement with experimental data is fairly good. On the other hand, for the free-to-oscillate cylinder, the structural response is dramatically dependent on the spanwise discretisation. The maximum amplitude of the structural response decreases as the mesh resolution increases, providing a closer fit with the experimental data. Also, the spanwise correlation of pressures is studied, finding remarkable differences depending on the level of spatial discretisation. Highlights: 3D LES simulations are used to obtain the static and VIV response of a rectangular cylinder of ratio 4. For the static cylinder the mean flow structures have been identified. The sensitivity of the simulations against different boundary conditions and spatial discretisations is assessed. Pressure correlation surfaces are provided for the static and VIV simulations. The VIV amplitudes is directly related with the level of correlation of the forces and pressures.